Sonorant spectra and coarticulation distinguish speakers with different dialects - Themistocleous, Charalambos; Fyndanis, Valantis; Tsapkini, Kyrana (My University, 2022)
This study aims to determine the effect of language varieties on the spectral distribution of stressed and unstressed sonorants (nasals /m, n/, lateral approximants /l/, and rhotics /r/) and their coarticulatory effects on adjacent sounds. To quantify the shape of the spectral distribution, we calculated the spectral moments from the sonorant spectra of nasals /m, n/, lateral approximants /l/, and rhotics /r/ produced by Athenian Greek and Cypriot Greek speakers. To estimate the co-articulatory effects of sonorants on the adjacent vowels' F1 - F4 formant frequencies, we developed polynomial models of the adjacent vowel's formant contours. All sonorants had distinct effects on adjacent vowel formant contours, especially for F3 and F4. The study highlights that the combination of spectral moments and coarticulatory effects of sonorants determines sonorants' linguistic (stress and phonemic category) and sociolinguistic (language variety) characteristics. It also provides the first comparative acoustic analysis of Athenian Greek and Cypriot Greek sonorants.
Keywords: Lateral approximants; Nasals; Polynomial models; Rhotics; Spectral moments